2016
DOI: 10.1007/s11892-016-0730-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Stem Cells: a Mixed Blessing in the Multifaceted World of Diabetic Complications

Abstract: Diabetes is one of the main economic burdens in health care, which threatens to worsen dramatically if prevalence forecasts are correct. What makes diabetes harmful is the multi-organ distribution of its microvascular and macrovascular complications. Regenerative medicine with cellular therapy could be the dam against life-threatening or life-altering complications. Bone marrow-derived stem cells are putative candidates to achieve this goal. Unfortunately, the bone marrow itself is affected by diabetes, as it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 111 publications
(134 reference statements)
1
18
0
Order By: Relevance
“…It was here hypothesized that T2DM impacts the bone marrow MSC (osteoblastic precursor) population, with potential implications for bone homeostasis in humans. This is in line with what has been observed in other complications associated with DM (reviewed in [29]) and in rodent models of T2DM [10,12]. Osteopathic comorbidities associated with T2DM include an increase in BMD [7], increased fracture risk [6,11] and delayed fracture repair [30].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It was here hypothesized that T2DM impacts the bone marrow MSC (osteoblastic precursor) population, with potential implications for bone homeostasis in humans. This is in line with what has been observed in other complications associated with DM (reviewed in [29]) and in rodent models of T2DM [10,12]. Osteopathic comorbidities associated with T2DM include an increase in BMD [7], increased fracture risk [6,11] and delayed fracture repair [30].…”
Section: Discussionsupporting
confidence: 85%
“…Currently, the field of MSC function is transitioning away from the idea that resident MSCs directly differentiate into repair tissue following injury but that their paracrine signalling is of greater importance to repair injury and to modulate immune responses (reviewed by Watson et al) [46]. Therefore, the paracrine angiogenic capacity of MSCs has been extensively explored with a view to creating a cellular therapy to treat the macro-and microvascular complications of DM as well as to understand the aetiology of the same [29]. Here, MSCs isolated from AMCs or from donors living with T2DM displayed a comparable capacity to induce an angiogenic response in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs represented a promising cell therapy opportunity due to the possibility to be isolated from various tissues. Additionally, their immunoprivileged status, multilineage potential and the ability to support angiogenesis in a paracrine fashion make them attractive therapeutically [ 3 ]. Despite leading to some encouraging results in animal models, MSCs achieved controversial benefit when cell therapy was translated in humans [ 3 ].…”
Section: Bm Perivascular Cell Stemness and Regenerative Potentialmentioning
confidence: 99%
“…Several multipotent cells have been proposed for the therapeutic applications of vascular regeneration in relieving the symptoms of ischemia, prevention of hypoxia-related tissue damage and avoidance of well-known vascular complications such as thrombosis, dissection or capillary leakage. Unfortunately, in spite of promising initial in vitro and ex vivo results, the adult stem cells failed to deliver an equally positive outcome in clinical studies [ 2 , 3 ]. From this point of view, endothelial progenitor cells (EPCs) offer a paradigm of this development.…”
mentioning
confidence: 99%
“…Transplanted ECs can improve recovery after injuries and disease and multiple studies in mouse models have shown improved reperfusion after ischemic limb injuries93435. However, these findings have not been borne out in clinical studies, as intramuscular delivery of bone marrow-derived cells to patients with peripheral artery disease is ineffective39. This discordancy could be due to the differences in injury-type, species or source cells.…”
Section: Discussionmentioning
confidence: 99%